2015
DOI: 10.1249/mss.0000000000000449
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of Respiratory Muscle Fatigue in a Mountain Ultramarathon Race

Abstract: Ultraendurance running reduces respiratory muscle strength for inspiratory muscles shown to result from significant peripheral muscle fatigue with only little contribution of central fatigue. This is in contrast to findings in locomotor muscles. Whether this difference between muscle groups results from inherent neuromuscular differences, their specific pattern of loading or other reasons remain to be clarified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
45
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 38 publications
4
45
1
Order By: Relevance
“…In particular, during a 2.5-hour treadmill run, simulating a marathon, a reduction in vital capacity of approximately 3% was reported after at least 90 min, while an average 8.6% reduction in post-race vital capacity was found after a marathon [46]. A similar reduction of approximately 10% was recently reported after an ultramarathon [3,7, 49]. In our study we observed a small but significant 4% reduction in vital capacity after an uphill and downhill run with an average duration of 95 min.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…In particular, during a 2.5-hour treadmill run, simulating a marathon, a reduction in vital capacity of approximately 3% was reported after at least 90 min, while an average 8.6% reduction in post-race vital capacity was found after a marathon [46]. A similar reduction of approximately 10% was recently reported after an ultramarathon [3,7, 49]. In our study we observed a small but significant 4% reduction in vital capacity after an uphill and downhill run with an average duration of 95 min.…”
Section: Discussionmentioning
confidence: 67%
“…Studies on uphill running and mountain ultramarathons have considered biomechanical and neuromuscular adaptations [41,42] as well as respiratory modifications [3,7]. To the best of our knowledge, no study has investigated ventilation and ventilatory pattern during the run.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Diaphragm fatigue is considered present with a post-exercise decline in P di, tw ≥ 15% [109]. Due to the invasive nature of esophageal balloon-tipped catheters, recent efforts have aimed to assess non-volitional declines in mouth pressure in response to cervical magnetic stimulation of the phrenic nerve [56, 119, 120], which were shown to be correlated with esophageal pressures [56]. Similarly, others have used a combination of sniff maneuvers and ultrasonography [79] to assess diaphragm fatigue.…”
Section: Introductionmentioning
confidence: 99%